LEADERSHIP IN RURAL TOURISM: A CASE STUDY OF WANGUN LESTARI VILLAGE, BANDUNG, WEST JAVA, INDONESIA - Yopy Maulana, Sari Ramadanty (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The role of village headman has been the important factor for the development of rural tourism. A village headman will face several challenges in developing the village, both as a leader in the institution and a community leader in the rural tourism area. This study aims to describe the role of leadership based on the concept of Performance Excellence of Baldrige. In addition, this research aims to determine the leadership style applied by the village headman in developing the potentials of rural tourism. This research used the qualitative method with a case study in Wangun Lestari Village. The data collecting technique used is an in-depth interview with rural apparatuses, communities related to rural development, and the villagers. The results showed that as a leader in a rural institutional organization, the headman performs an effective communication and focuses on action in the Performance Excellence. The research also revealed that the transformational leadership style applied by headman is a community-based leadership.